PENGARUH METODE EKSPERIMEN TERHADAP PRESTASI BELAJAR IPA SISWA KELAS IV SD IT SALSABILA 3 BANGUNTAPAN BANTUL YOGYAKARTA - Ajeng Hidayatun Afifah; Hidayati Hidayati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
The purpose of this study was descriptive to determine trends in science learning outcomes using the experimental method and lecture method. Comparatively to find out the differences in science learning achievement of fifth-grade students of SD IT Salsabila 3 Banguntapan Bantul Yogyakarta between learning using experiment method and lecture method. Technical data analysis is descriptive by comparing mean scores with ideal normal curves. Comparative data analysis using the t-test was previously conducted, the preliminary test of the analysis included the distribution normality test and variance homogeneity test. Descriptive research results indicate that the tendency of science learning achievement which learning using experiment method including the very high category and the lecture method including the high category. Comparatively, there are very significant differences in science learning achievement between the experiment method and lecture method, with t count = 4.8207 and p = 0,000. The average science learning achievement score in which learning uses the experiment method is higher than the lecture method, so it is concluded that there is an influence of the use of experiment on the science learning achievement of four complete semester students in Salsabila 3 Elementary School Yogyakarta 2018/2019.